Miejsce i znaczenie protestanckich przekładów Pisma Świętego w historii polszczyzny biblijnej (zarys opisu) - Koziara, Stanisław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The paper is an attempt at the synthetic look into this part of Polish bible translation heritage, whose integral part are the translations of the Bible in Protestant circles. The fundamental thesis of the work is based on the statement that Protestant translations of the Bible into Polish contributed substantially to its quantitative and qualitative evolution, as well as constitute one of the main sources of the development of the biblical stylistic variant of Polish. The greatest attention has been paid to the role and significance of Polish Bible translations in this process, which were made in the times of Reformation and Counter-Reformation, as well as to the attempt at indicating some links that appeared between the most important Catholic and Protestant translations of this period. The paper provides numerous references to previous views on the investigated issues, and provides a range of new suggestions, e.g. a periodization of the history of biblical Polish language, as well as indicates the need for further work in this field.